Association between High Doses Consumption of Niacin and Type 2 Diabetes - M Niknam, (Babol University of Medical Sciences, 2012)
BACKGROUND AND OBJECTIVE: Type 2 diabetes, characterized by insulin resistance, impaired insulin secretion, hyperglycemia and oxidative stress. Increasing prevalence of type 2 diabetes in parallel with expanding of food fortification with niacin has observed in developed and developing countries, so it is possible that intake of high doses of niacin may play a role as an environmental risk factor in type 2 diabetes. The purpose of the present study was to assess the association between consumption of high doses of niacin and the risk of type 2 diabetes.METHODS: The present study is a literature search in PubMed and Science direct with the use of niacin, diabetes, oxidative stress, insulin resistance and obesity as keywords. The results of animal and human studies published until 2011 in this field were considered. FINDINGS: Niacin by elevation of oxidative stress indices increases insulin resistance and leads to hyperinsulinemia, thereafter, improvement of oxidative stress indices by the antioxidant systems leads to elevation of insulin sensitivity that followed by hypoglycemia. Postprandial hypoglycemia induces excess energy intake and obesity. The elevation of oxidative stress indices, insulin resistance and obesity in long-term by continuous stimulation of pancreatic ? cells can lead to type 2 diabetes.CONCLUSION: Reducing niacin intake through reduction of niacin-rich foods and niacin fortified foods may be a useful preventive and therapeutic intervention in type 2 diabetes.